1200% enhancement of solar energy conversion by engineering three dimensional arrays of flexible biophotoelectrochemical cells in a fixed footprint encompassed by Johnson solid shaped optical well. (January 2021) - Suresh, Lakshmi; Vaghasiya, Jayraj V.; Kannan, Udayappan Praveen; Zhang, Yaoxin; Ravi, Sai Kishore; Paul, Nikita; Jones, Michael R.; Tan, Swee Ching
Abstract: Photosynthetic proteins carry out photochemical charge separation with a near-unity quantum efficiency and provide interesting materials for sustainable solar energy conversion in man-made photoelectrochemical devices. The three-dimensional architectures of natural photosynthesisers on both macroscopic and microscopic length scales contrast strikingly with the essentially two-dimensional architectures of commercial photovoltaic devices. In this work we fabricated flexible and semi-transparent bio-photoelectrochemical cells (BPEC) that showed excellent flexibility and durability in response to repeated mechanical deformation. A three-dimensional stack of five such BPECs connected in parallel produced a peak photocurrent of 2900 nA under simulated sunlight in the laboratory and 2400 nA when tested outdoors. Placement of the BPEC stack within either a regular solid reflective well or a Johnson solid reflective well further boosted these photocurrents, computational analysis indicating that the strongest boost that more than doubled output was the consequence of multiple reflections within the Johnson solid that increased the light intensity incident on the BPEC stack. These design features, inspired by natural structures for absorbing and reflecting sunlight, improved the relative performance of the BPECs under non-peak insolation, such that the photocurrent output under natural sunlight was relatively uniform between 10 a.m. and 5 p.m. We discuss how the flexibility, durability and partial transparency of the individual BPECs enable the fabrication of cell arrays with a range of three-dimensional architectures. Graphical Abstract: ga1 Highlights: Successfully fabricated 3 dimensional array of protein solar cells envisaging harnessing of unutilised reflected light. Demonstrates a low-footprint BPEC array inspired from two natural photo responsive systems. Such 3D architectures mitigate the need for sun trackers across the sky to homogenise the non-uniform current output. Transparency of the cells and their 3D arrangement aid in flatter current response throughout the day. 1200 % enhancement in the photocurrent achieved by integrating 3D stacked cells with Johnson solid optical wells.